MACRO-ECONOMIC DETERMINANTS AND MANAGEMENT OF NON-PERFORMING LOANS IN DEVELOPING ECONOMIES: ILLUSTRATIONS FROM NIGERIA - Onwumere, J.U.J,Chinyere C. Onyejiaku, Onyimba Roseline Chizoba,Ufodiama Cliffo rd Ndudi,Christian Ibe-Lamberts (International Journal of Advanced Science and Technology, 2020)
This study assesses macroeconomic determinants and management of non-performing loan ratio (NPLR) in Nigeria within the context of post-crisis (2009 - 2017) periods of 2008 global financial crisis. The precise objective was to determine the impact of macroeconomic factors (GDP growth, unemployment growth, exchange rate growth, lending rate growth, government expenditure, quantity money supply and inflation) on NPLR of the selected banks listed in Nigeria Stock Exchange. In line with the specific objective, one hypothesis was formulated. Data was gathered using purposive sampling technique where six banks were chosen. The sample covered 50% of the population for the period of eighteen years. The data were estimated with random effect model via generalized least square analysis with cross-sectional survey. Findings from the study revealed that unemployment growth rate, inflation rate, quantity of money supply and likewise government expenditure had positive and significant impact on non-performing loan rate. The other variables (GDP growth, exchange rate growth and lending rate growth), indicated negative effect on NPLR though, exchange rate growth was not a significant factor. It is recommended that macroeconomic variables must be taken into consideration.